Indonesia’s social protection system: the relevance of informal social protection to strengthen adaptation to climate change - Gusti Ayu Ketut Surtiari; Mia Wannewitz; Puguh Prasetyoputra; Tiodora Hadumaon Siagian; Matthias Garschagen (Journal of Integrative Environmental Sciences, 2024)
Social protection is praised as a multipurpose instrument to protect the most vulnerable people and ensure socioeconomic development. Recently, this approach has also been recognized by climate scientists. Over the past few decades, Indonesia, a highly exposed and vulnerable country facing climate change, has increased its efforts to protect all marginalized and vulnerable groups. However, the high uncertainty of social and economic impacts triggered by climate and environmental change increases pressure on the social protection system, leading to a rising need for deeper and broader coverage, especially among the most vulnerable people. This paper argues that vulnerable groups have built their own systems to be socially protected, which we refer to as informal social protection (ISP). Given that there is little reference to these particular structures in the literature on social protection, this study aims to explore their relevance and potential challenges. Jakarta, a highly urbanized and vulnerable city, was used as a case study. The city is simultaneously challenged by the increasingly adverse impacts of climate change. Gaps in formal social protection (FSP) will be analysed using qualitative and quantitative data to assess how and to what extent the most vulnerable groups are protected and whether ISP structures can fill the identified gaps. The results show that ISP can function as a solution to protect marginalized and vulnerable groups; however, more information is needed to ensure security considering long-term developments and increased future uncertainties.HIGHLIGHTS OF THIS STUDY FSP coverage in Indonesia still has gaps due to unregistered target groups, such as the missing middle population and informal sector workers.The uncertainty of the social and economic impacts caused by climate change increases pressure on the social protection system, leading to a greater need for broader coverage.ISP provides vulnerable groups with flexibility, local specificity, mutual benefits and reciprocity, collective decision-making, social cohesion, and trust.ISP involves community-based adaptation and support from NGOs to enhance ISP and make it more adaptive.ISP supports vulnerable groups affected by the unintended consequences of adaptation measures implemented by the government.